Automated Manufacture of Autologous CD19 CAR-T Cells for Treatment of Non-hodgkin Lymphoma - Jackson, Zachary; Roe, Anne; Sharma, Ashish Arunkumar; Lopes, Filipa Blasco Tavares Pereira; Talla, Aarthi; Kleinsorge-Block, Sarah; Zamborsky, Kayla; Schiavone, Jennifer; Manjappa, Shivaprasad; Schauner, Robert; Lee, Grace; Liu, Ruifu; et al. (Frontiers in Immunology, 2020)
Chimeric antigen receptor T cells (CAR-T cell) targeting CD19 are effective against several subtypes of CD19-expressing hematologic malignancies. Centralized manufacturing has allowed rapid expansion of this cellular therapy, but it may be associated with treatment delays due to the required logistics. We hypothesized that point of care manufacturing of CAR-T cells on the automated CliniMACS Prodigy® device allows reproducible and fast delivery of cells for the treatment of patients with non-Hodgkin’s lymphoma. Here we describe cell manufacturing results and characterize the phenotype and effector function of CAR-T cells used in a phase I/II study. We utilized a lentiviral vector delivering a second-generation CD19 CAR construct with 4-1BB costimulatory domain and TNFRSF19 transmembrane domain. Our data highlight the successful generation of CAR-T cells at numbers sufficient for all patients treated, a shortened duration of production from twelve to eight days followed by fresh infusion into patients, and the detection of CAR-T cells in patient circulation up to one-year post-infusion.